Analysis of Causes and Effects of Time Overrun in Construction Projects in Kaski District - Gurung, Atish; Poudel, Bishwash; Joshi, Buddi Raj; Aryal, Rajendra; Adhikari, Sundar (Journal of Engineering Issues and Solutions, 2026)
Construction projects frequently experience time overruns which often leads to cost escalation, disputes, and reduced project performance. This study aims to identify and analyze the major causes and effects contributing to schedule delays in Kaski district. From an extensive literature review, a total of 84 causes of time overrun were identified and categorized into seven groups related to: client/consultant, contractor, design, labor, material and equipment, external, and others (technical, contractual, legal). Similarly, 18 effects of time overrun were also identified for analysis. The study demonstrates the Relative Importance Index (RII) method was employed to rank the identified causes and effects based on their significance. Exploratory Factor Analysis (EFA) was conducted to group the 18 effects into distinct factors using the KMO test, Bartlett’s test of sphericity, eigenvalues, and varimax rotation. Confirmatory Factor Analysis (CFA) was then performed on the top five causes from each group and on the 18 effects of time overrun. Model fitness was evaluated using indices such as CMIN/df, CFI, IFI, TLI, SRMR, and RMSEA. Based on the responses of 75 respondents, following were the five most significant factors of causes of delays: frequent changes in project scope, adverse weather conditions, financial difficulties of contractors, bureaucratic delays in government approvals, delay in decision making by clients. Top five effects of delays were: cost overrun, legal claims & litigation, extension of overhead costs, disputes among stakeholders, inflation and price escalation impact. This study provides a validated structural framework that enhances the understanding of the dynamics of time overruns. The study concludes by emphasizing the need for better planning, communication, resource management, and coordination among project stakeholders to minimize time overruns in construction projects within Kaski District.